The 3D theory of osseointegration: material, topography, and time as interdependent determinants of bone–implant integration - Takahiro Ogawa; Makoto Hirota; Rune Shibata; Takanori Matsuura; Keiji Komatsu; Juri Saruta; Wael Att (International Journal of Implant Dentistry)
Abstract Despite widespread clinical success of dental implants, several fundamental questions remain unresolved: How does osseointegration—a biological phenomenon distinct from conventional bone healing—actually occur? Why does bone–implant contact never reach 100%? Why has there been minimal innovation in commercial implant surfaces over the past three decades? And why has the failure rate plateaued at around 8%? This review introduces the 3D Theory of Osseointegration, which conceptualizes implant integration as governed by three interdependent and dynamic determinants: material composition (Dimension 1), surface topography/roughness (Dimension 2), and time, which critically influences the physicochemical properties of implant surfaces (Dimension 3). For Dimension 1, the biocompatibility of various metals has been extensively studied, with commercially pure titanium and titanium alloys firmly established as the gold standard for dental implants. Dimension 3 underscores the long-overlooked impact of time—specifically, the biological aging of titanium surfaces caused by hydrocarbon accumulation and the loss of hydrophilicity—which significantly diminishes osteoconductivity. Importantly, recent studies have uncovered that this time-dependent degradation, once seen as an inevitable limitation, is in fact fully reversible. UV photofunctionalization restores surface hydrophilicity and removes hydrocarbon contaminants, revitalizing the bioactivity of titanium. This breakthrough not only resolves a long-standing barrier to optimal osseointegration but also establishes quantitative thresholds for key physicochemical parameters—such as carbon content and surface wettability. As a result, Dimensions 1 and 3—material and physicochemical properties—are approaching maturity in terms of optimization. In contrast, Dimension 2, surface topography, remains relatively underdeveloped despite decades of research and the clinical success of microrough surfaces. Now that UV photofunctionalization effectively mitigates biological aging and unlocks the full physicochemical potential of implant surfaces, the advancement of surface topography becomes the next critical frontier. This review critically examines each dimension, their interactions, and the limitations of current topographical design. It advocates for a shift from empirical to mechanism-driven engineering of implant surfaces and underscores the need for intentional synergy across all three dimensions. The 3D Theory of Osseointegration offers a structured framework to inform future implant design and research, aiming to better control and optimize the biological process of integration while acknowledging the complexities that still remain to be fully addressed.